PREPARATION OF ENGINEERING PERSONNEL FOR BLANK PRODUCTION: YESTERDAY, TODAY, AND WHAT TOMORROW? - B. M. Nemenenok (Литьë и металлургия)
The analysis of admission of students on specialty of the mechanical-technological faculty of BNTU (BelarusianNationalTechnicalUniversity) from 2005 to 2015 is carried out. It is shown that there is the decrease tendency in enlistment of enrollees and release of graduates for blank production.